التطرف الديني السياسي أنواعه في ضوء القرآن الكريم: طلبة جامعات مدينة غزة نموذجاً: Political Religious Extremism in Light of the Quran: Students of Gaza City Universities as a Model - Abumarzouq, Mona Jamal; Abdullah, Mustaffa; Abu -Alhaj, Thabet Ahmed (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
The Holy Quran is a fundamental source for Muslims which included complete and healing guidelines in all matters of life. Due to effected by deviant and destructive doctrines of political religious extremism, some people depart from the principles of the Qur’an culminated in a departure from obedience to God and the provisions of Islamic law. Hence, it is a necessary to reveal the perception of the phenomenon of political religious extremism in the light of Quran, and how the Quran presented this phenomenon in all its forms, especially in the current circumstances that have reached its gravity. From this point of view, this paper delves into a deep research for the purpose of encapsulating decisive knowledge along with alarming deviate teaching of religion. The research is aimed at identifying Quranic depiction on political religious extremism and counter argument for misunderstanding of Islamic teachings and provisions. Through inductive and descriptive analytical approach, fieldwork with lecturers and students of universities in Gaza City, this study demonstrates a real manifestation of political religious extremism phenomenon resurrecting an extension of awareness among lecturers and students at the university level in Gaza City. One of the most important findings of this research is religious extremism develops under political, social or economic circumstances and the situation in Gaza has led to an increase of prevalence in religious extremism. This study also identifies a discrepancy among the age groups between the first and second level whose inclination are less towards political religious extremism. It connects with possible causes behind political religious extremism and departure from obedience to God and the provisions of Islamic law that is social media. Additionally, the deficiency of scholars and preachers using social media, systematic and scientific approaches delay the prevention process of counter-extremism or cutting the root of its causes.